Agribusiness Supply Chain Management of “Rainbee”: Apis cerana in Forests of Bondowoso, Indonesia - Hasanah, Niswatin; Prasetyo, Budi; Nurkholis, Nurkholis; Atmaji, Ery Setiyawan Jullev (International Journal of Studies in Social Sciences and Humanities (IJOSSH), 2025)
In Indonesia, the Apis cerana honey supply chain faces structural challenges, including low producer digital literacy, limited market access, and dependence on intermediaries. The objective of this study is to evaluate the efficacy of the Apis cerana honey distribution supply chain and to establish a digitalisation system that incorporates text notifications and e-commerce to increase farmers’ income. The research employed a survey methodology, utilising primary data collectedthrough questionnaires, interviews, and field observations of honey farmers in Kretek Village, Bondowoso. We calculatedthe marketing margins and the farmer’s share across three distribution channels to determine their efficiency. The results showed that the traditional channel (Channel I) had the highest marketing margin and the lowest farmer’s share. In contrast, the use of e-commerce (Channel III) increased the farmer’s share by more than 40% by eliminating twomarketing institutions: distributors and retailers. The push notification system was effective in accelerating the exchange of information between producers and consumers and encouraging repeat purchases from the same store. This studycontributes to the formulation of an effective and sustainable supply chain model for Apis cerana honey producers, aligned with SDG Target 8 concerning decent labour and economic growth.